2013
DOI: 10.1080/14680777.2013.838378
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Voice: Technologically mediated empowerment and transformation among young Arab women

Abstract: This feminist, qualitative study sheds light on how young Arab women used cyberactivism to participate in the wave of political and social transformations widely known as the Arab Spring. It argues that these activists leveraged social media to enact new forms of leadership, agency, and empowerment, since these online platforms enabled them to express themselves freely and their voices to be heard by the rest of the world, particularly the global media. This resulted in a multidimensional personal, social, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…They, thereby, actively act as agents in youth communities. Blogging about serious and even fatal illness enabled Regine Stokke and Alice Pyne to gain health, social strength and control in a technologically mediated transformation 40 41…”
Section: Pathographies Empowerment and Agencymentioning
confidence: 99%
“…They, thereby, actively act as agents in youth communities. Blogging about serious and even fatal illness enabled Regine Stokke and Alice Pyne to gain health, social strength and control in a technologically mediated transformation 40 41…”
Section: Pathographies Empowerment and Agencymentioning
confidence: 99%
“…Kemajuan di bidang kesetaraan gender dan politik itu memberikan kemajuan yang positif, misalnya penelitian menunjukkan potensi media sosial untuk menantang dominasi laki-laki di bidang politik (Demirhan & Çakır-Demirhan, 2015) dan mengubah demokrasi supaya lebih memberikan peran kepada perempuan (Radsch & Khamis, 2013).…”
Section: Pendahuluanunclassified
“…She found that through their online discussions, users were able to redefine their positions and "circulate revised normative interpretations" for the victim-blaming rhetoric that dominates mainstream media (p. 800). In the Arab world, despite women's low literacy level, disadvantaged economic situation, and physical and sexual threats as well as intimidation during the Arab Spring revolutions, their use of social media was very effective in raising women's voices, educating women about their rights, and empowering them with discourses to counter negative practices against them (Khamis 2014;Newsom and Lengel 2012;Radsch and Khamis 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%